Empowering organizations through corporate social responsibility - Wolf, R.; Issa, Theodora; Thiel, M. (2014)
© 2015 by IGI Global. All rights reserved. The impact of businesses on a country's economy extends beyond just the monetary effects of the company. The ethical standard to which a business upholds itself can have a crucial impact on the development of a country's economy. Empowering Organizations through Corporate Social Responsibility addresses the implementation of businesses' ethical standards in both emerging and advanced economies, interpreting the social impact of this issue in a global context. Highlighting case studies, interdisciplinary perspectives, and strategies in business management, this book is a pivotal reference source for academics, researchers, post-graduate students, and professionals concerned with the development of the business sector.